Feasibility of cage culture of Asian seabass in coastal rivers of Bangladesh - Ghosh, Ashim Kumar; Dey, Bipul Kumar; Shahid, Rahat Bin; Bain, Saikat; Roy, Babu Kumar; Sarower, Md. Golam (Journal of Fisheries, 2026)
Despite its aquaculture potential, Asian seabass (Lates calcarifer) has not yet been adopted for cage culture in Bangladesh. This pilot study aimed to assess the feasibility of cage culture of this species in coastal rivers of Bangladesh. A total of six cages (18 m3 each) were installed in a coastal river and each was stocked with 50 fish (7.70 ± 0.18 g). Three feeding treatments were applied: 100% live feed (live and/or trashed juvenile tilapia) (T1); 50% live feed with 50% formulated feed (T2); and 100% formulated feed (T3). The experimental fish were reared for 12 weeks and fed at 8% of their body weight during the initial 3 weeks and at 6% during the later weeks. Fish refused formulated feed. Survival in T3 (64%) was significantly lower compared to that in T1 (88%) or T2 (82%) but did not differ between T1 and T2. Mean specific growth rates (SGR) were 1.66, 1.12, and 0.90 % d–1; daily growth rates (DGR) were 2.20, 0.74, and 0.44 g, and weight gain (WG) values were 182.50, 61.10, and 36.50 g in T1, T2, and T3, respectively. SGR values significantly differed among the treatments. DGR and WG values in T1 were significantly higher than that in T2 or T3 but did not differ between T2 and T3. Results indicate that cage culture of Asian seabass in Bangladesh requires live and/or trash fish as feed, or else advances in domestication and artificial feed development.